How internationalised school teachers construct cross-cultural identities in an internationalised school in Shanghai, China - Poole, A (2019)
This thesis explored how four internationalised school teachers constructed cross-cultural teacher identities in an internationalised school in Shanghai, China (pseudonym, WEST). The topic of international teacher identity is of significance to practitioners, researchers and school leaders alike as there is growing consensus that teacher identity and its construction is not only a vital part of developing a professional self, but is a complex, open-ended life-long project, involving cognitive, affective and, increasingly in a globalising world, intercultural dimensions. However, the international education literature continues to construct the international educator in positivist terms due to a focus on macro-level phenomena, such as international schools, curricula and the nature of international education. The essentialisation of international teachers as a type or a ‘reduced Other’ (Grimshaw, 2007) has resulted in their lives and experiences being silenced and marginalised in the literature.